Implicações da resolução do MDT na modelagem de instabilidade de vertentes - Tiago D. Martins; Bianca Carvalho Vieira.; José Eduardo Bonini.; Carlos Bateira (Confins)
The mathematical models physically based are important tools to indicate potentially unstable areas using geotechnical and topographic information. Therefore, a digital elevation model is essential, since it is the base to obtain information as contribution area and slope angle, considered fundamental in its application. This work aimed to evaluate the response of the mathematical model physically based SHALSTAB with different size cell (resolution) on the Digital Terrain Model (DTM) derived from conventional topographic data (contour lines) in a watershed with shallow landslide record. The results indicate that there was no significant improvement in the definition of unstable areas when the DTM grid resolution changes (10, 5 and 1m).